META-ANALISIS PENELITIAN AKUNTANSI DI INDONESIA PERIODE TAHUN 2014-2016 - Kornelius Geraldo Adrian Pratama; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2018)
Accounting research published in the world's top accounting journal according to Moser (2012) is less innovative. Moser said that research topics were concentrated in the scope of earnings management, analytical or management thinking, compensation, regulation, governance or budgeting. In addition, research methods and basic theories used in accounting research tend to use only certain types. With the existence of these problems, encourage the writer to do a mapping of accounting research in Indonesia. The purpose of this research is to find out the trends of accounting research in Indonesia, especially in 2014-2016.This study uses descriptive qualitative methodology with meta-analysis techniques. The data used in this study are secondary data which is taken from the Proceding Simposium Nasional Akuntansi (SNA), Jurnal Akuntansi dan Keuangan Indonesia (JAKI) and Jurnal Akuntansi Multiparadigma (JAMAL) for the 2012-2016 period.The mapping results of this study state that accounting research in Indonesia in the 2014-2016 period tends to use quantitative research with the basic theory of agency theory. The field of financial accounting and capital market studies (AKPM) is the most studied field of study. Secondary data research sources are most widely used with document review data collection techniques. In addition the corporation is the object of research that is the most studied.